Effect of exercise prescription intervention mode in the Omaha System in elderly patients with delayed gastric emptying after choledocholithiasis surgery - Kan, Wenjing; Sun, Huacui; Chen, Ruimei (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to explore the impact of exercise prescription intervention mode according to the Omaha System on defecation recovery in elderly patients with delayed gastric emptying (DGE) after choledocholithiasis surgery.MethodsA total of 96 elderly patients with DGE after choledocholithiasis surgery admitted to our hospital from July 2019 to June 2022 were selected and split into the control group (CG) and observation group (OG). The CG adopted a routine nursing intervention. Based on the CG, patients in the OG adopted an exercise prescription intervention based on the Omaha System. The postoperative defecation recovery time, negative emotions, sleep quality, quality of life, and nursing satisfaction of patients in both groups were compared.ResultsRelative to the CG, the postoperative defecation recovery time of the OG was shorter (P < 0.05). Self-rating anxiety scale, self-rating depression scale, and Pittsburgh sleep quality index scores in the OG were lower compared with the CG after intervention (P < 0.05). Each dimension of the 36-item short form score in the OG was higher compared with the CG after intervention (P < 0.05). The nursing satisfaction of patients in the OG was higher compared with the CG (P < 0.05).ConclusionThe Omaha System-based exercise prescription intervention significantly accelerated gastrointestinal function recovery and improved quality of life in elderly patients with postoperative DGE, suggesting it is a valuable and recommended adjunct to routine postoperative care.